Climate change boredom: Exploring its predictors and the psychological factors that influence intention to act - Ruxandra Malina Petrescu-Mag; Dacinia Crina Petrescu; Hamid Rastegari; Adrian Ivan; Ioan Valentin Petrescu-Mag (PLoS ONE, 2026)
Multiple psychological factors, from fear to hope, play a role in actions addressing climate change. However, an understanding of how these factors interact to shape such behaviors remains limited. This gap holds significant implications for advancing both research and climate practice. The present study aims to contribute to the overall effectiveness of climate change mitigation and adaptation efforts by providing an understanding of the factors influencing individuals’ intentions to act against climate change, and casting light upon a less explored dimension – climate change boredom. Climate change boredom highlights a psychological barrier that can hinder climate action. Intention to act is a key step toward a change in behavior and effective environmental efforts. Therefore, we determined the factors that predicted climate change boredom and investigated the influence of climate change boredom on people’s intention to act against climate change. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) on data obtained from a survey of a representative sample of Romanian people, the study found that beliefs about climate change, climate change goal commitment, self-efficacy of cooperation, perceived health impacts of climate change, living environment, and age predicted 66.8% of climate change boredom. Results showed that climate change boredom significantly hindered the intention to act against climate change. From a practical perspective, identifying predictors of climate change boredom and intention to act is important in developing strategies, policies, and communication approaches that reinvigorate individuals’ and communities’ motivations to participate in climate action efforts. Moreover, addressing climate change boredom is essential for ensuring long-term environmental security, as disengagement from climate issues can weaken societal resilience and hinder adaptive strategies in the face of climate threats.